On New Sandwich Results of Univalent Functions Defined by a Linear Operator - Mihsin, Bassim Kareem; Atshan, Waggas Galib; Alhily, Shatha S. (Iraqi Journal of Science, 2022)
In this research paper, we explain the use of the convexity and the starlikness properties of a given function to generate special properties of differential subordination and superordination functions in the classes of analytic functions that have the form in the unit disk. We also show the significant of these properties to derive sandwich results when the Srivastava- Attiya operator is used.